2020
DOI: 10.3390/molecules25225365
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Drug Discovery from Microbial Sources: The Unique Mangrove Streptomycetes

Abstract: Worldwide cancer incidence and mortality have always been a concern to the community. The cancer mortality rate has generally declined over the years; however, there is still an increased mortality rate in poorer countries that receives considerable attention from healthcare professionals. This suggested the importance of the prompt detection, effective treatment, and prevention strategies. The genus Streptomyces has been documented as a prolific producer of biologically active secondary metabolites. Streptomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 146 publications
(176 reference statements)
1
46
0
Order By: Relevance
“…These natural products include chemotherapeutic agents from plant, marine, and bacterial sources [ 7 ]. Although only limited numbers of the isolated compounds from microbes can be directly utilized as clinically effective medicines in their own right (naturally occurring form), streptomycetes are verified producers of anticancer drugs such as bleomycin (glycopeptides group), dactinomycin (non-ribosomal peptides group), mitomycin C (quinones group), and doxorubicin (anthracyclines group) [ 1 ]. Therefore, in this study, we aimed to isolate and identify two major metabolites of S. griseus isolate KJ623766, a recovered soil isolate previously screened in our lab that exhibited promising cytotoxic activity against various cancer cell lines [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These natural products include chemotherapeutic agents from plant, marine, and bacterial sources [ 7 ]. Although only limited numbers of the isolated compounds from microbes can be directly utilized as clinically effective medicines in their own right (naturally occurring form), streptomycetes are verified producers of anticancer drugs such as bleomycin (glycopeptides group), dactinomycin (non-ribosomal peptides group), mitomycin C (quinones group), and doxorubicin (anthracyclines group) [ 1 ]. Therefore, in this study, we aimed to isolate and identify two major metabolites of S. griseus isolate KJ623766, a recovered soil isolate previously screened in our lab that exhibited promising cytotoxic activity against various cancer cell lines [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cancer mortality rate has generally declined over the years; however, there is still an increased mortality rate in poorer countries that receives considerable attention from healthcare professionals [ 1 ]. This suggests the importance of prompt detection, effective treatment, and successful prevention strategies [ 1 ]. Natural products, particularly microbial metabolites, have been the mainstay of cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Gifted with the ability to form spores, streptomycetes are ubiquitous in nature and produce a diverse array of secondary metabolites that can be exploited for the benefit of humanity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . One of the significant breakthroughs in streptomycetes research is the discovery of streptomycin (from the soil bacterium, Streptomyces griseus) by Professor Waksman and his teamwhich subsequently led him to the Nobel Award in Medicine later in 1960 [13,[17][18][19][20][21] .…”
Section: Short Introductionmentioning
confidence: 99%
“…In other words, cancer is responsible for nearly one of the six deaths, leading to its recognition as one of the world's most prominent "killers" [1,2] . In addition to that, it has been suggested that nearly 65% of the increase in deaths related to all cancer types will occur in less developed regions of the world by the year 2030 while developing countries are anticipated to face an estimated burden of 23.6 million new cases per year [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%